A liberdade em John Stuart Mill na contemporaneidade - Ferreira, Nicholas Gabriel Minotti Lopes [UNESP] (2014)
The proposal of this work is manage a thematic study upon the concept of liberty. Such object is too dearly to the philosophy, since it is commonly associated it with norms, conduct patterns, inquiries upon moral and ethical rules, action possibilities, chooses, deliberations and etc. Therefore, to investigate the nature of the liberty, many philosophers has built with their arguments is the way to propel the aspects mentioned above adding with them the social and individual perspectives. This means that the liberty should have rules or limits treated as frontiers (in social perspective) or determinations (individual case) bounded tightly with liberty in relation to a context or particularities of an individual/social action. This kind of interpretation supposes the exam upon liberty in actions that will be or has already been done cutting off the action in a movement of separating it from the individual (and all of its aspects) and analyses carefully that fragment of activity seeking for liberty. This kind of analysis allows, in one hand, an ‘intellectual comfort’ assuring that the individual acted freely or not; in other hand, ignores many fundamental aspects that constitute the liberty. Such aspects can be, for example, the power to change an action which is already in course, customs, opinions and, mainly, fails inherent to the human nature. In this way, this work has as criteria questioning (and why not value) these aspects to observe the nature of liberty in actions within its course and it the meanwhile the arguments to be show here endorses the suspect that the liberty is larger in systems or group of rules that guide the actions. In this way, John Stuart Mill, English philosopher from 19th century, thinks that the individuality would be a fundamental element to the social well-being such as expressed in his book On liberty (1963). The individuality emerges through the opinions expressed in social context. Therefore, when...